Visceral fat loss by whole‐body electromyostimulation is attenuated in male and absent in female older Non‐Insulin‐Dependent diabetes patients. Issue 6 (12th October 2022) - Houdijk, Alexander P. J.; Bos, Nanneke F. J. M. E.; Verduin, Wouter M.; Hijdendaal, Mick M.; Zwartkruis, Michiel A. L.
Abstract: Introduction: Type 2 diabetes and its reversal correlate with increases and decreases in visceral fat (VF). Resistance exercise reduces VF in healthy persons, but little is known in type 2 diabetes. Muscle contractions induced by whole‐body electromyostimulation (WB‐EMS) provide a very effective form of resistance training. We hypothesized that WB‐EMS reduces VF and improves plasma glucose measures in older non‐insulin dependent diabetes mellitus (NIDDM) males and females. Methods: A four‐arm age‐matched case control study was done on WB‐EMS twice a week in older NIDDM patients (27 males, 18 females) compared with controls (15 males, 15 females). VAT area (VAT, cm 2 ), total fat mass (TFM, kg) and lean body mass (LBM, kg) were assessed by DEXA‐scanning. HbA1c, fasting glucose and plasma lipoproteins were measured at baseline and after 4 months. Results: Baseline control VAT was higher in males than females (140.5 ± 35.6 vs. 96.7 ± 42.3, p  < .001). In NIDDM, VAT was higher with no significant sex difference (206.5 ± 65.0 vs. 186.5 ± 60.5). In controls, WBEMS reduced VAT in males and females to similar extent (−16.9% and −16.4%, p  < .001 vs. baseline) and in preference to TFM (−9.2% and −3.6%) or body weight loss (−2.8 and −2.1%). In NIDDM, VF loss was attenuated in males (−7.3%, p  < .01) but completely absent in females. WBEMS reduced HbA1c and cholesterol and increased HDL levels (all p  < .05) only in male NIDDM Conclusions: WBEMS induced VF loss in healthy older males and females an effect strongly attenuated in male and completely absent in female NIDDM patients. This questions the effectiveness of muscle contraction‐induced VF lipolysis in NIDDM. Sex differences may dictate the success of resistance training in NIDDM, a subject that needs to be addressed in future studies. Abstract : Our data for the first time show that whole‐body electromyostimulation lowers visceral fat mass in healthy elderly men and women. However, in type 2 diabetes patients this effect was significantly lower in male and completely absent in female patients. Sex differences in muscle‐induced fat lipolysis in type 2 diabetes deserves more attention as this will direct preventive and therapeutic approaches.